Pathohistomorphometric and Immuno-Histologic Changes in Early Arteriovenous Fistula Failure in Patients with Chronic Kidney Disease - Pushevski, Vladimir; Dejanov, Petar; Rambabova Bushljetic, Irena; Petrushevska, Gordana; Popov, Zhivko; Ivanovski, Ninoslav (Macedonian Academy of Sciences and Arts/Walter de Gruyter GmbH, 2024)
Hemodialysis is a prevalent treatment for the end-stage chronic kidney disease (CKD) worldwide. The primary arteriovenous fistula (AVF), widely considered the optimal hemodialysis access method, fails to mature in up to two-thirds of the cases. The etiology of the early AVF failure, defined as thrombosis or inability to use within three months post-creation remains less understood, and is influenced by various factors including patient demographics, surgical techniques, and genetic predispositions. Neointimal hyperplasia is a primary histological finding in stenotic lesions leading to the AVF failure. However, there are insufficient data on the cellular phenotypes and the impact of the preexisting CKD-related factors. This study aims to investigate the histological, morphometric, and immunohistochemical alterations in the fistula vein, pre-, peri-, and post-early failure. Materials and Methods Eighty-nine stage 4-5 CKD patients underwent standard preoperative assessment, including the Doppler ultrasound, before a typical radio-cephalic AVF creation. Post-failure, a new AVF was created proximally. The vein specimens were collected during the surgery, processed, and analyzed for morphometric analyses and various cellular markers, including Vimentin, TGF, and Ki 67. Results The study enrolled 89 CKD patients, analyzing various aspects of their condition and AVF failures. The histomorphometric analysis revealed substantial venous luminal stenosis and varied endothelial changes. The immunohistologic analysis showed differential marker expressions pre- and post-AVF creation. Conclusion This study highlights the complexity of the early AVF failures in CKD patients. The medial hypertrophy emerged as a significant preexisting lesion, while the postoperative analyses indicated a shift towards neointimal hyperplasia. The research underscores the nuanced interplay of vascular remodeling, endothelial damage, and cellular proliferation in the AVF outcomes.
Keywords: fistula failure; CKD; Vimentin; TGF; intimal hyperplasia